2015
DOI: 10.1371/journal.pone.0124338
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced IMP3 Expression Activates NF-кB Pathway and Promotes Renal Cell Carcinoma Progression

Abstract: BackgroundInsulin-like growth factor 2 mRNA binding protein 3 (IMP3) is expressed in metastatic and a subset of primary renal cell carcinoma (RCC). However, the role of IMP3 in RCC progression was poorly understood. We aim to uncover the mechanism of IMP3 in regulating clear cell RCC (CCRCC) progression and validate the prognostic significance of IMP3 in localized CCRCC.MethodsCaki-1 cells stably overexpressing IMP3 and Achn cells with knockdown of IMP3 were analyzed for cell migration and invasion by Transwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…Our findings in glioma cells with IMP3 overexpression and silencing unequivocally establish IMP3 as a positive modulator of NF-κB signalling by increasing the translation of p65 transcript. These results are in coherence with the observations made by Pei et al, where they have shown that IMP3 activates NF-κB pathway and contributes to migration of renal cell carcinoma cells [52]. Our p65 rescue experiment in IMP3 depleted U138 glioma cells clearly reflects the importance of the molecule downstream to IMP3 in imparting migratory potential to these cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings in glioma cells with IMP3 overexpression and silencing unequivocally establish IMP3 as a positive modulator of NF-κB signalling by increasing the translation of p65 transcript. These results are in coherence with the observations made by Pei et al, where they have shown that IMP3 activates NF-κB pathway and contributes to migration of renal cell carcinoma cells [52]. Our p65 rescue experiment in IMP3 depleted U138 glioma cells clearly reflects the importance of the molecule downstream to IMP3 in imparting migratory potential to these cells.…”
Section: Discussionsupporting
confidence: 93%
“…It had been reported that knockdown of IMP3 in cervical cancer, breast cancer and melanoma cell lines could reduce cell migration and invasiveness [ 38 40 ]. In renal cell carcinoma, IMP3 can also promote cell migration and invasion by activation of NF-κB pathway [ 41 ]. As recently reported, knockdown of IMP3 decreased cell proliferation, migration, and invasion, and increased the sensitivity to platinum in ovarian cancer through increased expression of hCTR1 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…IMP3 is thought of as a bona fide oncofetal protein that is overexpressed and is involved in cell proliferation, migration, and invasion in several kinds of tumors ( 18 , 23 , 28 , 29 ). In regard to skin squamous neoplasms, the role of IMP3 in cutaneous SCC, using various cell biological and molecular biological approaches, has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have described the mechanism of cell proliferation and invasion of IMP3 expression in cells. Recent studies have revealed that IMP3 promoted the progression of melanoma by regulating high mobility group AT-hook 2 (HMGA2) ( 18 ), the cell migration of renal cell carcinoma by activation of the NF-κB pathway ( 28 ), cell invasion and migration after epithelial to mesenchymal transition (EMT) ( 29 ), and matrix adhesion, cell motility and invasion of pancreatic carcinoma by enhancing CD44 and the transcription of kinesin KIF11 expression ( 23 ).…”
Section: Discussionmentioning
confidence: 99%